Five Challenges for Benefits Management in Complex Digitalisation Efforts – and a Research Agenda to Address Current Shortcomings. Issue 2 (2019) - Askedal, Kirsti; Flak, Leif Skiftenes; Aanestad, Margunn
No abstract available